Penerapan Sistem Akuntansi Dasar pada Usaha Kecil Menengah di kota Banjarmasin - Sri Ernawati; Jumirin Asyikin; Octavia Sari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2016)
The following research was conducted to gain an overview of the application of accounting systems in small and medium enterprises engaged in trading business built Jakarta Cooperative Micro Small and Medium Enterprises in Banjarmasin. The research uses descriptive method with a sample of 60 respondents. With the scale of cumulative or Guttman scale is known that the application of accounting systems in small and medium enterprises engaged in trading business built offices Cooperative Banjarmasin city is on a scale of 0,064 or are on the no association or low association (weak association) which shows that the application of the accounting system base on small and medium enterprises in the field of trade business Banjarmasin city is still relatively low. Guidance and cooperation of the parties involved, especially the service cooperatives, small and medium micro Banjarmasin city, is expected to continue to provide guidance and more intensive training with regard to the application of the accounting system to a group of small and medium enterprises in general, especially for small and medium enterprises engaged in the trading business in the city of Banjarmasin.